Методологія кримінологічних досліджень: в пошуках нових парадигм - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (My University, 2025)
Стаття узагальнює сучасні концепції парадигмальних візій кримінології і кримінального права від кількісних методів дослідження до валідації через призму методології креативного девелопменталізму та адаптації теорії творчого руйнування (creative destruction) Шумпетера, Агіона та Говіта до сучасних парадигм кримінологічних досліджень. Пропонується динамічний підхід до оновлення методології кримінологічних досліджень, коректуючи помилкові механізми отримання даних для послідовного формулювання нових валідних підходів поводження з правопорушниками. Акцент ставиться на балансі прав суб’єктів кримінально-правових відносин, зрушуючи у бік ціннісно-орієнтованої справедливості, контекстуалізації криміналізації і процесуальної результативності (ЄСПЛ, Helme v. Estonia, 2025). Методологічні аспекти включають якісні методи (Einat, 2025: інтерв’ю, етнографія для «чому» та «як» злочинності); помилки неофіта (ототожнення статистики з реальністю, кореляція vs. причинність, латентність, політична селективність); гомеокінетичний підхід (Ібералл, 1972) до злочину як обміну речовиною, енергією, інформацією в системі «злочинець–жертва–середовище», кримінологічну інженерію з критикою за редукціонізм на макрорівні. Для України ключовими є виклики постконфліктної реінтеграції, декриміналізації насильства, регулювання нових категорій злочинів. Стаття закликає до уважності при застосуванні методів системи збору, методів збору даних та інтерпретації з урахуванням нових парадигм, віктиморієнтованої юстицїї, та інтеграції практики ЄСПЛ і сталого розвитку системи кримінальної юстиції України. The article summarises contemporary paradigmatic visions in criminology and criminal law, ranging from quantitative research methods to validation through the lens of the methodology of creative developmentalism and the adaptation of the theory of creative destruction to modern criminological research paradigms. A dynamic approach to updating criminological methodology is proposed, correcting erroneous data-generation mechanisms in order to consistently formulate new, valid approaches to offender management. The emphasis is placed on maintaining a balance of rights among the subjects of criminal-law relations, shifting towards value-oriented justice, contextualised riminalisation, and procedural effectiveness (ECtHR, Helme v. Estonia, 2025). The methodological section includes qualitative methods (Einat, 2025: interviews, ethnography for the «why» and «how» of crime); typical novice errors (equating statistics with reality, correlation vs. causation, latency, political selectivity); the homeokinetic approach (Iberall, 1972), which conceptualises crime as an exchange of matter, energy, and information within the «offender–victim–environment» system, with accompanying criticism for macro-level reductionism on criminal engeneering and insufficient empirical verifiability. Further attention is given to the epistemological limits of contemporary crime data, including algorithmic misclassification in digitalplatform crime reporting, the rising instability of post-conflict criminal trajectories, and the distortion of public risk perception through media-driven crime amplification. The article argues for an integrated model of criminological inquiry that combines robust quantitative design, triangulated qualitative methods, and iterative validation cycles to avoid methodological drift and ensure resilience of theories in rapidly transforming social realities. From a criminal-law perspective, the article highlights the growing role of contextual proportionality, especially in transitional states, where over-criminalisation and selective enforcement can undermine public trust and the legitimacy of institutions. The proposed framework emphasises the interaction between criminalisation grounds, victim-oriented justice, and the evolving ECtHR doctrine on procedural fairness and the minimum consistency standards for the use of coercive powers. For Ukraine, the key challenges include post-conflict reintegration, the de-normalisation and deromanticisation of violence, and the regulation of new categories of technologydriven offences. Particular emphasis is placed on the need to identify, validate, and correct systematic biases in law-enforcement data, improve the media crime index to reflect actual victimisation patterns, and align criminal-justice reforms with EU principles of subsidiarity, proportionality, and sustainability via victim-orientedjustice. The article concludes by advocating for greater methodological attentiveness in data collection and interpretation, aligned with emerging paradigms, victim-oriented justice, and the integration of ECtHR practice into the sustainable development of Ukraine’s criminal-justice system.
Methodology of criminological research: in search of new paradigms – an article
Туляков В. О. Методологія кримінологічних досліджень: в пошуках нових парадигм / В. О. Туляков // Вісник Асоціації кримінального права України. - 2025. - № 2(24). - С. 289-334. - Режим доступу: https://doi.org/10.21564/2311-9640.2025.24.343624 ; https://hdl.handle.net/11300/31424
Keywords: креативний девелопменталізм; творче руйнування; контекстуальна криміналізація; ціннісно-орієнтована юстиція; гомеокінетичний підхід; якість методології; медіа-індекс злочинності; методологія якості; цифрові ризики; ЄСПЛ; creative developmentalism; creative destruction; contextual criminalisation; value-oriented justice; homeokinetic approach; methodological quality; media crime index; digital risks; ECtHR